Evaluation of Essential Oil and Methanol Extracts of Thymus kotschyanus for Chemical Compounds and Antibacterial Activity - Ozturk, Suzan; Ozturk, Avni (Asian Journal of Chemistry, 2010)
The essential oils obtained from the aerial parts of Thymus kotschyanus were analyzed for chemical compounds by using GC and GC-MS. In addition, following the methanol extraction of aerial parts of Thymus kotschyanus, soluble fraction was tested for its antibacterial activity by using disc diffusion assay. Twenty-three components accounting for 98.34% of oil were identified. The main compounds were thymol (40.39%), carvacrol (28.15%), p-cymene (10.76%) and γ-terpinene (8.13%). The antibacterial activity results showed that methanol extract of Thymus kotschyanus had a great potential of antibacterial activity against 38 of 52 bacteria species, in particular, Arthrobacter atrocyaneus, Bacillus cereus, Bacillus flexus, Bacllus lentimorbis, Brevibacillus brevis, Erwinia chrysanthemi, Kocuria rosea, Micrococcus lylae, Paenibacillus macerans, Pantoea agglomerans, Pseudomanas syringae syringae, Staphylococcus cohnii cohnii, Xanthomonas arboricola carylina and methanol extract inhibited growth of these bacteria at the concentration of 15.60-500 μg/mL. The results suggest that Thymus kotschyanus represents an inexpensive source of natural mixtures of antibacterial compounds that exhibit potentials for use in food systems to prevent the growth of food-borne bacteria and extends the shelf life of the processed food.